Synthesis of CdTe-CdSe core-shell quantum dots with luminescence in the red - Norhayati Abu Bakar,; Akrajas Ali Umar,; Muhamad Mat Salleh,; Muhammad Yahaya, (Universiti Kebangsaan Malaysia, 2010)
This paper reports on the synthesis and characterization of CdTe-CdSe core-shell quantum dots (QDs) with luminescent from 650 to 720 nm. The QDs were synthesized using a wet-chemical process at a moderate temperature (300 °C) following two-steps process of core and shell synthesis. The photoluminescence characterization on the QDs showed that the QDs emitted light in the range of red regime with quantum yield as high as 37%. Owing to their unique photoluminescence characteristics (high quantum yield and narrow spectrum), the QDs may find a potential application in a variety of applications such as LED, solar cell and bio-labeling.